“Partly American!”: Sarah Bernhardt’s Transnational Disability in the American Press (1915-1918) - Ramos-Gay, Ignacio (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2018)
The aim of this paper is to analyze the representation of Sarah Bernhardt’s physical disability in the American press prior to and during her last tour in the United States (1915-1918), and how the amputation of her right leg ignited a series of allegories associating the actress with both French and American national identities. Bernhardt’s maimed physicality was rapidly construed as a metaphor of the mutilated French soldiers of the Great War and of a devastated France itself. However, as I will show, one of the prosthetic devices crafted by American manufacturers symbolically turned the tragedienne into “partly an American citizen” as well as into a token of modern western technology. Bernhardt’s artificial leg encapsulated a number of cultural, economic and national attributes linking therapy with American industrial capitalism, and her conceptualization as an American icon thanks to prosthetics reflects the use of non-normative bodily metaphors to encourage national belonging in the press. Keywords: American press; Transatlantic Studies; Sarah Bernhardt; disability; prosthetics